Characteristics of GLONASS Inter-frequency Code Bias and Its Application on Wide-lane Ambiguity Resolution - XU Longwei (Acta Geodaetica et Cartographica Sinica, 2018)
GLONASS inter-frequency code biases (IFCBs) vary with receiver manufacturers,firmware versions,and antenna types.IFCBs are hardly corrected or modeled precisely,so that Hatch-Melbourne-Wübbena (HMW) combination observation contains a systemic bias and cannot applied into GLONASS wide-lane ambiguity resolution.Utilizing the residuals of GLONASS HMW combination observations,we propose an algorithm to estimate IFCB of different sites (DS-IFCB).The experiment results show that DS-IFCB is long term stability and the sizes of DS-IFCBs in some homogeneous baselines (composed by same type of devices,i.e.receiver type,version and antenna) are larger than 0.5 meters.In order to achieve wide-lane ambiguities in real-time,DS-IFCBs,estimated with previous observations,are used as priors to cancel IFCBs in current observations.After DS-IFCB offset,both the success rate and correct rate of GLONASS wide-lane ambiguity resolutions are improved,regardless of whether baselines are equipped with homogeneous devices.The correct rates of all baselines are higher than 98%.